2012
DOI: 10.1253/circj.cj-11-0339
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Preoperative Percutaneous Cardiopulmonary Support on Outcome Following Left Ventricular Assist Device Implantation

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp echanical circulatory support with a left ventricular assist device (LVAD) has become a well-established procedure for patients with end-stage heart failure. Patient selection and timing of implantation, however, remain critical issues. Although several studies have identified pre-implantation risk factors in regard to mortality, 1,2 most are limited by the fact that few of the reported patients were supported by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 19 publications
1
8
2
Order By: Relevance
“…Hemodynamic indices are reported to be reliable and strong predictors for severe right heart failure after LVAD insertion. 17,18,[22][23][24] However, in the present study, all hemodynamic values before durable LVAD in the BTB group were better than those in the nonbridging group, because the majority of BTB cases received right ventricular unloading by ECMO or CentriMag RVAD. These findings suggest that hemodynamic indices do not reflect true right ventricular function, and we may underestimate the possibility of biventricular failure in patients in refractory cardiogenic shock.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Hemodynamic indices are reported to be reliable and strong predictors for severe right heart failure after LVAD insertion. 17,18,[22][23][24] However, in the present study, all hemodynamic values before durable LVAD in the BTB group were better than those in the nonbridging group, because the majority of BTB cases received right ventricular unloading by ECMO or CentriMag RVAD. These findings suggest that hemodynamic indices do not reflect true right ventricular function, and we may underestimate the possibility of biventricular failure in patients in refractory cardiogenic shock.…”
Section: Discussioncontrasting
confidence: 65%
“…4 Others showed that an INTERMACS profile I or preoperative ECMO use was a risk factor for requiring postoperative RVAD after durable LVAD insertion. 4,22,23 In these reports, preoperative central venous pressure level was a predictor of postoperative severe right ventricular failure requiring RVAD. Hemodynamic indices are reported to be reliable and strong predictors for severe right heart failure after LVAD insertion.…”
Section: Discussionmentioning
confidence: 97%
“…Possible mechanisms of interaction with warfarin involve metabolic inhibition and induction, vitamin K intake, and changes in plasma protein binding. However, the protein binding rate of linezolid is relatively low (31%) (19). In the present study, no significant difference was observed in the albumin level between before and after the initiation of linezolid therapy.…”
Section: Discussioncontrasting
confidence: 68%
“…In other words, the decision for PCPS insertion by a physician that automatically assigns a patient profile 1 does not necessarily predestine the worst prognosis. 24 Currently, implantable VADs have not been indicated in patients with profile 1 in Japan, and therefore the poor prognosis in the profile 1 group might be a consequence of extracorporeal LVAD use. We look forward to analyzing the prognosis of patients with profile 1 under the application of implantable continuous-flow LVADs.…”
Section: Imamura T Et Almentioning
confidence: 99%